Focus on the relationships between the cell wall composition in the extraction of anthocyanins and tannins from grape berries. (16th April 2023) - Boulet, Jean-Claude; Abi-Habib, Elissa; Carrillo, Stéphanie; Roi, Stéphanie; Veran, Fréderic; Verbaere, Arnaud; Meudec, Emmanuelle; Rattier, Anais; Ducasse, Marie-Agnès; Jørgensen, Bodil; Hansen, Jeanett; Gall, Sophie Le; et al.
Highlights: Arabinose, mannose, glucose, were correlated to polyphenol extractions in model solutions. Pectin and hemicellulose CoMPPs were correlated to polyphenol extractions. CoMPPs values were related to the maturation, e.g. mAb LM19 and JIM11. Polyphenol extractions would benefit of bindings yielding low aggregates. Abstract: Concentrations of anthocyanins and tannins after extraction from berries in wines and from skin macerations in model solutions have been studied for two grape varieties, two maturation levels and two vintages berries. Characterization of the cell wall polysaccharides has also been performed, the classical method based on the analysis of the neutral sugars after depolymerization being completed by a comprehensive microarray polymer profiling (CoMPP). Extraction was lower in model solutions than in wines, with the same ranking: non acylated anthocyanins > tannins > p-coumaroylated anthocyanins. The polysaccharidic composition suggested a role of homogalacturonans, rhamnogalacturonans and extensins in the extraction process. A global explanation of the interactions between anthocyanins, tannins and polysaccharides is proposed.